Samokontrola sądowa w ramach skargi kasacyjnej — wybrane zagadnienia - Bulejak, Radosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
This article focuses on the matter of judicial self-review in the proceedings of administrative courts. From 15 August 2015 administrative courts can change their own rulings, when a party brings a cassation appeal. In this article the following topics are discussed: the admissibility of self-review; the basics of self–review; proceedings of self-review and appealing against the ruling issued as a result of self-review.
Keywords: postępowania przed sądami administracyjnymi; samoocena sądów administracyjnych; podstawy samooceny; kasacja; skargi